Comparison of automated flowcytometric reticulocyte analysis with manual reticulocyte count - Patel, Komal; Patel, Siddhi M. (International Journal of Research in Medical Sciences, 2019)
Background: Reticulocytes are young or immature red blood cells released from bone marrow and that contain remanants of ribonucleic acid (RNA) and ribosomes. Reticulocyte count (RC) is the index of erythropoietic activity within bone marrow. The reticulocyte counting methods at clinical laboratories are currently divided into manual and automated. Methods: A total of 500 samples of study cases were processed by manual method using New Methylene Blue (NMB) and automated method based on flowcytometry by PENTRA XLR HORIBA hematology analyzer. All quality control parameters were evaluated and values obtained by both methods were compared using various statistical methods. Results: Automated hematology analyzer provides excellent precision and linearity with no significant carryover. On comparing manual and automated RC method good method correlation was found (correlation coefficient r-0.865), however individual case wise percent deviation between manual and automated RC and CRC varied significantly. In addition within run precision calculated for automated RC differed significantly from manual count. The mean of difference between duplicate readings (150 samples) of manual and automated RC (<5%) were 0.3 and 0.01 respectively while 6.3 and 0.15 respectively for >5% RC. Thus, automated method was found to be more precise than the manual RC. Conclusions: The manual count method for RC associated with significant imprecision compared to flowcytometric method mostly based on interobserver variation and the smaller number of cell being counted. In contrast, the automated method is rapid, easy to operate, count higher number of cells with precise measurement.